Hybridization ddRAD‐sequencing and phenotypic analysis clarify the phylogeographic structure and evolution of an alpine Chrysanthemum species with a sky island distribution - Hu, Xue-Ying; Lu, Wen-Xun; Wang, Zi-Zhao; Rao, Guang-Yuan (Frontiers in Plant Science, 2025)
The phylogeographic structure of a species is the result of historical intraspecific differentiation and influences the pace and trajectory of speciation. Therefore, study of the phylogeographic structure of species and the mechanisms underlying its formation can shed light on the evolutionary history and speciation of species, as well as enhance our understanding of the generation and maintenance of species diversity. Chrysanthemum hypargyrum is an alpine species endemic to central China. It is restrictively distributed to three isolated mountain ranges, and its populations exhibit a sky island distribution and some morphological variation to different environments. In this study, we investigated the morphogenetic divergence, phylogeographic structure, and evolutionary history of this species through hybridization ddRAD-sequencing, phenotypic analysis, and species distribution modeling. Our results indicate that C. hypargyrum originated in the Daba Mountains and has since diverged into three lineages. The phylogeographic structure and distribution of this species are mainly attributed to geographic isolation, the founder effect and Quaternary climate oscillations as its range expanded. The divergence of its three major lineages coincided with Pliocene mountain uplifts and Pleistocene climatic fluctuations. The current sky island distribution has also promoted the diversification and phylogeographic structure of C. hypargyrum.